Influence of With Pair Jump Rope Training and Ladder Drill Model on Kids Athletic Improvement - Regina Septiria; M Subandowo; Ujang rohman (Jp.jok (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan), 2020)
This study aims to develop a variety of athletic sports learning through pair jump rope and ladder drill training models to improve the kids athletics of elementary school students. The method used was an experimental method through a quantitative approach with a randomized group-pretest-posttest design research design. The population was 32 elementary school students with a sample of grade IV and V students selected by stratified proportional sampling, divided into two groups, each given a pair jump rope model (X1) and ladder drill model (X2). The data collection technique used the Kids Athletics Test IAAF instrument which was analyzed using the t and anava tests at the sig level. α = 0.05. The results of the analysis t count > t Sig..0.05 ( > sig 0.05) means that the pair jump rope training model and the ladder drill training model can improve the kids athletic abilities of elementary school students. Mean while, the analysis of variance test results for each element of kids athletic obtained Fcount > Fsig.0.05 ( > sig 0.05), which means that there is a significant difference between the paired jump rope athletic training model and the ladder drill training model to improve the kids athletic of elementary school students.